Development of Scientific-Based Learning Devices Implemented in the Inquiry-Flipped Classroom Learning Model to Improve Science Literacy in Acid-Base Material - Epinur; Fuldiaratman; Isra Miharti; Minarni (Postgraduate, University of Mataram, 2024)
The trend in science education policy in the 21st century emphasizes the importance of scientific literacy in science education as a transferable outcome. This research is a type of Research and Development (R&D) development research. Development research in the field of education aims to produce products for the benefit of education. This research produces a new product in the form of e-LKPD with a scientific approach to acid-base material. The purpose of this research and development is to find out how the procedure for developing teaching materials based on a scientific approach is implemented in the inquiry-flipped classroom learning model to improve Science Literacy skills and to find out the practicality of teaching materials based on a scientific approach implemented in the inquiry-flipped classroom learning model. Based on the results of the validation carried out on material and media experts in two rounds, the results of the first material validation were 89.30%, the second material validation was 98.70%. Design validation was conducted in two rounds where the first round obtained results of 87.50% and the second round of design validation 97.50%. Based on the results obtained from chemistry teachers, the first practitioner validation obtained 87% and the second practitioner validation obtained 91%, student responses to teaching materials with a percentage of 85.50%. Based on the criteria for the interpretation of the percentage of practicality, the group evaluation (student responses) was obtained with practical criteria or feasible for revision